Kedudukan Hak Tanggungan dalam Perampasan Aset Tindak Pidana Korupsi: Perspektif Keadilan dan Kepastian Hukum: Studi Kasus BPR Perumda Purworejo (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
Corruption cases in Indonesia often involve the recovery of state assets, including properties encumbered by mortgages (hak tanggungan). This research conducts a normative legal analysis on how current law treats such pledged assets when they become objects of state confiscation in corruption crimes. We examine Indonesian legislation (especially the Tipikor Act, TPPU Act, and Mortgage Act), judicial practice, and principles of justice and legal certainty. The Bank Perumda BPR Purworejo case is used as an illustrative case study: here fictitious loans and misused collateral led to state losses of hundreds of millions of rupiah, and investigators seized assets (including four mortgaged properties) as evidence. The analysis finds that existing rules inadequately protect good-faith creditors: courts have noted that a corruption verdict does not automatically erase a prior mortgage lien, and that a certified mortgage confers a preferential right equal to a judgment. In practice, however, law enforcement often seizes all assets of the convict without first verifying third-party rights, creating legal uncertainty and perceived injustice. We argue that fair outcomes require stricter safeguards for creditors (e.g. mandatory review of collateral status before seizure) and consideration of equitable principles. In conclusion, we recommend legal reforms or guidelines to balance the state’s recovery goals with protection of bona fide mortgagees, so as to uphold substantive justice while maintaining legal certainty.